Vitamin B12 Deficiency and Hemoglobin H Disease Early Misdiagnosed as Thrombotic Thrombocytopenic Purpura: A Series of Unfortunate Events - Andreadis, Panagiotis; Theodoridou, Stamatia; Pasakiotou, Marily; Arapoglou, Stergios; Gigi, Eleni; Vetsiou, Evaggelia; Vlachaki, Efthymia (Case Reports in Hematology, 2015)
We herein would like to report an interesting case of a patient who presented with anemia and thrombocytopenia combined with high serum Lactic Dehydrogenase where Thrombotic Thrombocytopenic Purpura was originally considered. As indicated a central venous catheter was inserted in his subclavian vein which led to mediastinal hematoma and finally intubation and Intensive Care Unit (ICU) hospitalization. After further examination patient was finally diagnosed with B12 deficiency in a setting of H hemoglobinopathy. There have been previous reports where pernicious anemia was originally diagnosed and treated as Thrombotic Thrombocytopenic Purpura but there has been none to our knowledge that was implicated with hemothorax and ICU hospitalization or correlated with thalassemia and we discuss the significance of accurate diagnosis in order to avoid adverse reactions and therapy implications.